Systemic Administration of Ribbon-type Decoy Oligodeoxynucleotide Against Nuclear Factor κB and Ets Prevents Abdominal Aortic Aneurysm in Rat Model - Miyake, Takashi (Nature Publishing Group, 2011)
Currently, there is no effective clinical treatment to prevent abdominal aortic aneurysm (AAA). To develop a novel therapeutic approach, we modified decoy oligodeoxynucleotide (ODN) against nuclear factor κB (NFκB) and ets, to a ribbon-shaped circular structure without chemical modification, to increase its resistance to endonuclease for systemic administration. Intraperitoneal administration of ribbon-type decoy ODNs (R-ODNs) was performed in an elastase-induced rat AAA model. Fluorescent isothiocyanate (FITC)-labeled R-ODNs could be detected in macrophages migrating into the aneurysm wall, and NFκB and ets activity were simultaneously inhibited by chimeric R-ODN. Treatment with chimeric R-ODN significantly inhibited aortic dilatation, whereas conventional phosphorothioate decoy ODN failed to prevent aneurysm formation. Significant preservation of elastic fibers was observed with chimeric R-ODN, accompanied by a reduction of secretion of several proteases from macrophages. Activation of matrix metalloproteinase (MMP)-9 and MMP-12, but not MMP-2, was suppressed in the aneurysm wall by chimeric R-ODN, whereas recruitment of macrophages was not inhibited. Treatment with chimeric R-ODN also inhibited the secretion of cathepsin B and K from macrophages. Overall, the present study demonstrated that systemic administration of chimeric R-ODNs prevented aneurysm formation in a rat model. Further modification of the decoy strategy would provide a means of less invasive molecular therapy for human AAA.